Controlled water-soluble properties of poly(vinyl alcohol) films via the benzoxaborole-containing temperature-responsive copolymers. (26th June 2019) - Kudo, Yoko; Ono, Junya; Kotsuchibashi, Yohei
Abstract: Functionalized poly(vinyl alcohol) (PVA) films were prepared using benzoxaborole-containing temperature-responsive copolymers via reversible covalent bonding between benzoxaborole and diol groups. Poly(2-(2-methoxyethoxy)ethyl methacrylate) (poly(MEO2 MA)) and poly(oligo(ethylene glycol) methacrylate) (poly(OEGMA)) copolymers were selected as the temperature-responsive polymers and prepared by the reversible addition-fragmentation chain transfer (RAFT) polymerization with different benzoxaborole contents (5-methacrylamido-1, 2-benzoxaborole (MAAmBO)). The melting point ( T m ) and enthalpy changes (Δ H ) of the PVA film decreased on mixing with benzoxaborole-based copolymers. The solubility of the benzoxaborole-based copolymer/PVA films in aqueous solutions could be controlled by varying the temperature and pH. The physicochemical properties of the functionalized PVA films were studied by 1 H nuclear magnetic resonance ( 1 H NMR), gel permeation chromatography (GPC), ultraviolet–visible (UV–vis) spectroscopy, differential scanning calorimetry (DSC), and Fourier transform infrared (FT-IR) spectroscopy. To the best of our knowledge, this is the first report of functionalized benzoxaborole-based copolymer/PVA films and their controllable water-soluble properties that were imparted by the mixed copolymers. Graphical abstract: Image 1 Highlights: Functionalized poly(vinyl alcohol) (PVA) films were prepared using benzoxaborole-containing copolymers. The physicochemical properties of the functionalized PVA films were investigated. The T m and |Δ H | of PVA decreased by mixing the benzoxaborole-based copolymers. The water-soluble properties were controlled by the benzoxaborole-diol interaction and temperature-responsive properties.